K3 Imagine : self-service bot - Garðar Sigurðsson 1984-; Davíð Birgisson 1994-; Ólafur Brynjar Jónsson 1994- (2019)
The Self-service bot is a project that was initially done in the fall of 2018 and is a chatbot that assists users in browsing and buying products through a messaging platform such as Facebook’s Messenger by using natural language. We took it upon us to improve the current version of this bot as well as adding some additional features. The project was worked on for, and in cooperation with K3 Business Technologies Group and is a final project in BSc of Computer Science at Reykjavík University.